The prognostic significance of adrenocortical carcinomas identified incidentally. Issue 7 (17th October 2018) - Rossfeld, Kara K.; Maithel, Shishir K.; Prescott, Jason; Wang, Tracy S.; Fields, Ryan C.; Weber, Sharon M.; Sicklick, Jason K.; Yopp, Adam C.; Duh, Quan‐Yang; Solorzano, Carmen C.; Votanopoulos, Konstantinos I.; Hatzaras, Ioannis; et al.
Abstract : Background and Objectives: Little is known regarding the difference in prognosis among patients who have an incidentally discovered adrenocortical carcinoma (ACC) vs those who present with signs or symptoms. We aimed to explore differences in the outcomes of these two populations. Methods: Data were collected on patients who underwent resection of ACC at 1 of 13 institutions between January 1993 and December 2014. Presentations were categorized as incidental vs symptomatic and outcomes were compared. Results: Among 227 patients, 100 were diagnosed incidentally while 127 patients presented with symptoms/signs. Clinical and pathological features were comparable among incidental vs nonincidental patients with ACC following the exceptions. Patients with incidentalomas were more likely to have a T1/T2 tumor (55.8% vs 34.8%; P  < 0.01) and less likely to have a functional tumor (33.7% vs 47.9%; P  = 0.04). Patients with an incidental ACC had improved median recurrence‐free survival (RFS; 29.4 months) compared with patients with a nonincidental ACC (13.0 months; P  = 0.03); however, on multivariable analysis, incidental ACC was not an independent predictor of survival. Conclusions: Patients with resected ACC identified incidentally had an improved RFS compared with the patients who presented with symptoms or signs. This difference may be related to the patients with incidental tumors having earlier T‐stage disease.